Legal liability arising from the transmission of new Coronavirus infection – Study in Egyptian civil law – - Mohamed, Magda Kadri Ibrahim (Journal of Economic, Administrative and Legal Sciences, 2021)
The study aimed to identify the adaptation of the liability arising from the transmission of the new coronavirus infection and to indicate the parties to the claim of this responsibility, and to determine who is responsible for the damages arising from the transmission of the infection, and the forms of compensation.The study examines the basis of compensation in liability, and clarifies the el ements of liability arising from mers-coV infection In addition to identifying the most important one of the most important findings of the study was that tort liability for transmission of the new coronavirus infection arises from a legal and moral obliga tion, and it is not permissible to agree on exemption from liability, and the affected coronavirus has the right to claim compensation for material and moral damage when the elements of tort are available. Most importantly, the study recommended that state governments should enact laws that address disease outbreaks and epidemics, and develop various legal safeguards to address the serious effects caused by epidemics in general and the emerging coronavirus in particular.
Keywords: novel coronavirus; tort; compensation; fault; damage